PS 05-56 CENTRAL BLOOD PRESSURE AND WAVE REFLECTIONS AFTER FULL COURSE MARATHON RACE. (September 2016) - Park, Jae Hyoung; Cho, Jae-Young; Lee, Seunghun; Joo, Hyung Joon; Hong, Soon Jun; Yu, Cheol Woong; Lim, Do-Sun
Abstract : Objective: Marathon running is aerobic and extremely vigorous exercise. Central blood pressure and wave reflections are independent predictors of cardiovascular risk. We investigated the acute effect of marathon race on central blood pressure and wave reflections. Design and Method: We studied 30 trained amateur marathoners (male n = 28, mean age = 51.6 ± 8.3 years). We measured central blood pressure and augmentation index before and immediate after the Seoul international marathon (18 th March 2012). Central blood pressure and AIx (augmentation index) were measured using HEM-9000AI (Omron Healthcare Co., Ltd., Kyoto, Japan). Wilcoxon signed rank test was used to determine the difference between before and after race for blood pressure and AIx. Results: There is no significant change of brachial systolic and diastolic blood pressure before and after marathon. (p = 0.259, 0.494, respectively) However, there is a significant reduction of central systolic blood pressure after race (128.5 ± 16.8 to 115.5 ± 14.5 mmHg; p < 0.001). Marathon race caused a significant fall in both AIx (77.3 ± 11.3 to 57.4 ± 13.4 %; p < 0.001) and AIx@75 (72.0 ± 9.3 to 58.1 ± 12.2 %; p < 0.001). Conclusions: The present study found a reduction in central systolic blood pressure without changes of brachial blood pressure. A significant fall in wave reflections was observed after marathon race. There were more or less acute beneficial effects of marathon on cardiovascular system contrary to our concern.